Lipofilling: A New Therapeutic Option for the Treatment of Lupus Panniculitis-Induced Atrophy - Laura Polivka; Marc Revol; Maxime Battistella; Hervé Bachelez (Karger Publishers, 2016)
Lupus panniculitis is a rare manifestation of cutaneous lupus erythematosus, which may lead to major aesthetic sequelae with a severe impact on patients' quality of life. We report 2 cases supporting the short- and long-term efficacy and safety of lipofilling in the treatment of lupus panniculitis-induced atrophy. These observations pave the way for prospective, larger-scale studies in patients with scarring lupus panniculitis, provided that the autoimmune pathogenic process is in complete, stable remission.